2012
DOI: 10.1002/etc.1943
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Tenax model to assess bioavailability of PCBs in field sediments

Abstract: Bioavailability has been estimated in the past using equilibrium partitioning-based biota-sediment accumulation factors. These values are not always reliable using field-collected sediments, however, likely due to varying amounts of different organic carbons, particularly black carbon, in sediments. Therefore, improving approaches to better evaluate contaminant bioavailability in sediment are needed. In the present study, a literature-based model was constructed that relied on both laboratory-exposed and field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Although the ability of Tenax extractions to predict bioaccumulation of pyrethroids, despite biotransformation, has previously been demonstrated [22], it was unclear how biotransformation would impact the ability of the bioaccumulation Tenax model to predict bioaccumulation. The results of the comparison showed that 100% of the pyrethroid data fell within the 95% confidence interval of the bioaccumulation Tenax model, suggesting that this model could account for the bioaccumulation of a variety of chemical classes by multiple species [22,25]. The pyrethroid data considered bioaccumulation of permethrin and bifenthrin by L. variegatus and Hexagenia sp.…”
Section: Can the Bioaccumulation Tenax Model Be Used For Other Compoumentioning
confidence: 91%
See 4 more Smart Citations
“…Although the ability of Tenax extractions to predict bioaccumulation of pyrethroids, despite biotransformation, has previously been demonstrated [22], it was unclear how biotransformation would impact the ability of the bioaccumulation Tenax model to predict bioaccumulation. The results of the comparison showed that 100% of the pyrethroid data fell within the 95% confidence interval of the bioaccumulation Tenax model, suggesting that this model could account for the bioaccumulation of a variety of chemical classes by multiple species [22,25]. The pyrethroid data considered bioaccumulation of permethrin and bifenthrin by L. variegatus and Hexagenia sp.…”
Section: Can the Bioaccumulation Tenax Model Be Used For Other Compoumentioning
confidence: 91%
“…In a log-log linear regression, the bioaccumulation Tenax model correlates the concentration in the organism on a lipid-normalized basis against the amount recovered from Tenax normalized to the amount of sediment organic carbon in the sample. Where the model was less successful at estimating bioaccumulation within the confidence interval, it overestimated, rather than underestimated, exposure [25]. Specifically, 95% of the bioaccumulation data fell within the 95% confidence limits of the model.…”
Section: How Well Does Tenax Estimate Bioavailability?mentioning
confidence: 94%
See 3 more Smart Citations